Sleep Duration during Pregnancy using an Activity Tracking Device - Kominiarek, Michelle A.; Yeh, Chen; Balmert, Lauren C.; Facco, Francesca; Grobman, William; Simon, Melissa (American Journal of Perinatology Reports, 2020)
Objective The aim of this study was to describe sleep duration across gestation in women who wore an activity-tracking device (ATD) during pregnancy, and to study the association between sleep duration and adverse maternal and neonatal outcomesStudy Design Women ≥ 18 years old who owned a smartphone were approached to participate in 2016 to 2017. Participants received instructions to wear and sync an ATD daily. Steps, sedentary hours, and sleep duration were wirelessly transmitted via cellular technology. We measured sleep duration for the main episode of sleep and excluded sleep times < 120 minutes. Mixed models were used to assess the trajectory of mean weekly hours of sleep by gestational age. Secondary analyses evaluated differences in pregnancy outcomes between insufficient (< 7/24 hours) and sufficient sleep (≥ 7/24 hours) groups, based on mean hours of sleep within the first 7 days of ATD use.Results The majority of 94 participants self-reported minority racial–ethnic status (33% non-Hispanic black and 51% Hispanic), had government insurance (83%), were nulliparous (61%), and had pre-pregnancy overweight or obesity (56%). The mean (standard deviation) duration of sleep was 7.2 ± 2.4 hours per 24 hours. In mixed models analyses, gestational age was statistically significantly associated with mean hours of sleep (β = −0.02; 95% confidence interval: −0.04 to −0.01; p < 0.001). Women who had < 7 hours of sleep had greater median daily steps compared with those who had ≥ 7 hours of sleep (median: 7,122; interquartile range [IQR]: 5,167–8,338 vs. median: 5,005; IQR: 4,115–7,059; p < 0.01), but there were no significant differences in other outcomes (sedentary time, gestational weight gain, pregnancy associated hypertension, gestational diabetes, gestational age at delivery, cesarean delivery, or mean birthweight), p  > 0.05 for all comparisons.Conclusion The mean sleep duration was 7.2 ± 2.4 hours among the 94 women in this cohort and decreased with advancing gestational age. Further research is required to evaluate sleep measurements with ATD in pregnant women and how sleep duration and quality is related to maternal and neonatal outcomes.
Keywords: pregnancy; sleep; activity tracking device